45.9k views
2 votes
Does anyone know the answer to this?

Does anyone know the answer to this?-example-1
User Moacyr
by
8.6k points

1 Answer

4 votes
To solve -2x(2-4x)-3, we can first multiply the bracket by -2x:

-2x(2-4x)-3
= -2x(2)-(-2x)(4x)
= -4x+8x^2-3

We can then rearrange the numbers:

= 8x^2 -4x -3

Then factorize it by quadratic equation:


\frac{ (- 4) \sqrt[ \binom{ + }{ - } ]{ { - 4}^(2) - 4(8)( - 3)} }{2(8)} \\ x = 0.911... \: or \:x = 0.411...
Therefore x=0.911 or x=0.411.

Hope it helps!
User Myloginid
by
8.2k points